2016
DOI: 10.1080/00325481.2016.1240590
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of obese patients at moderate or higher Findrisc score based on their atherogenic index

Abstract: Most of the women presented with clearly less unfavorable atherogenic risk than men. Two different phenotypes of obese women with at least moderate Findrisc score were revealed, and the level of inflammation seems to be the main discriminant factor. Larger prospective studies are required to elucidate whether those are really two different pathogenically phenotypes or if they belong to the same phenotype's continuum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Most previous studies grouped individuals based on a few metabolites, mainly parameters of lipid and carbohydrate metabolism, or single specific metabolite classes like plasma lipoproteins or fatty acids . Few studies have included several parameters originating from different metabolic pathways, extensive metabolic data, or “‐omics” data, whereas anthropometric data were included in many studies in the clustering process . We expected that such extensive data may provide a more comprehensive characterization of individuals in the metabotyping process and, thus, a more refined and generalized metabotype definition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most previous studies grouped individuals based on a few metabolites, mainly parameters of lipid and carbohydrate metabolism, or single specific metabolite classes like plasma lipoproteins or fatty acids . Few studies have included several parameters originating from different metabolic pathways, extensive metabolic data, or “‐omics” data, whereas anthropometric data were included in many studies in the clustering process . We expected that such extensive data may provide a more comprehensive characterization of individuals in the metabotyping process and, thus, a more refined and generalized metabotype definition.…”
Section: Discussionmentioning
confidence: 99%
“…This allowed us to identify disease‐related metabotypes. Studies examining the prevalence were limited to at most three diseases, mainly diabetes, hypertension, or the metabolic syndrome, and only one previous study examined the risk of incident hypertension . Van Bochove et al., for example, identified three plasma lipoprotein clusters with varying lipid response to fenofibrate therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study performed by Yıldız et al [16] in our country, it was shown that cardiovascular risk increases significantly in postmenopausal women compared to premenopausal women. The studies indicate that cardiovascular risk in men is significantly higher than in women in all groups of age [17,18]. We also determined that cardiovascular risk is 5.570 times more in men than in women.…”
Section: Discussionmentioning
confidence: 76%
“…The implementation of this method in future trials would provide more reliable information which may help in creating more successful, individualised treatment strategies for established groups (patterns) of patients. 50…”
Section: Discussionmentioning
confidence: 99%